ETIKA BERMEDIA SOSIAL DI RUANG PUBLIK UNTUK ANTISIPASI CYBERBULLYING (STUDI FENOMENOLOGI GENERASI Z) - Marsha Yoan Ezraria, (2024)
The development of communication technology has changed the way of interaction between individuals or groups. Interactions that are usually carried out face to face are now carried out indirectly, namely using the internet through social media. Social media provides a freer and more open interaction space for users to convey and receive information. Cyberbullying is a form of crime that puts other people down with the aim of humiliating the victim. Cyberbullying leave digital traces that are difficult to remove and have a wide reach. This causes victims to have a greater risk of suffering from stress, depression and even suicidal thoughts due to fear and shame. This research investigates social media ethics, how to apply social media ethics in anticipating cyberbullying.